2015
DOI: 10.1016/j.rbr.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas depressivos e de ansiedade e apoio social estão associados de modo independente à qualidade de vida específica da doença em pacientes colombianos com artrite reumatoide

Abstract: More depressive and anxiety symptoms were independently associated with lower disease-specific QOL, while higher perceptions of having people to do activities with (belonging social support) and higher SES were independently associated with higher disease-specific QOL. Psychosocial factors impact QOL in RA above and beyond disease activity. Additional research into the benefits of psychosocial assessment of RA patients and provision of comprehensive care to improve QOL is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Our study found a mean state anxiety score of 35.2 and trait anxiety score of 36.7. These values are similar to the findings of Rogers et al, who found values of 35.3 and 38.4 respectively among Columbian patients who were also recruited by the ACR/EULAR 2010 classification criteria [ 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our study found a mean state anxiety score of 35.2 and trait anxiety score of 36.7. These values are similar to the findings of Rogers et al, who found values of 35.3 and 38.4 respectively among Columbian patients who were also recruited by the ACR/EULAR 2010 classification criteria [ 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…It was verified the predominance of women in this sample and similar results to other studies. [2,3,[26][27][28] According to Mota et al, [9] RA preferentially affects women in a ratio of 3:1. In the same way, authors affirm that SLE also affects women, but young ones and in a ratio of 10:1.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of the participants was around 45 years, with a predominant age group of 30 to 59 years old, similar to other studies. [27,28,[31][32][33] According to Mota et al [9] RA affects all age groups, but it has a higher prevalence from 40 to 60 years. However, SLE prevails during the fertile age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations